The right to narcissism : a case for an im-possible self-love - DeArmitt, Pleshette, 1967- (Fordham University Press, 2014)
This book aims to wrest the concept of narcissism from its common and pejorative meanings - egoism and vanity - by revealing its complexity and importance. The author undertakes the work of rehabilitating "narcissism" by patiently reexamining the terms and figures that have been associated with it, especially in the writings of Rousseau, Kristeva, and Derrida. These thinkers are known for incisively exposing a certain (traditional) narcissism that has been operative in Western thought and culture and for revealing the violence it has wrought - from the dangers of amour-propre and the pathology of a collective "one's own" to the phantasm of the sovereign One. Nonetheless, each of these thinkers denounces the naive denunciation of "narcissism," as the dangers of a non-negotiation with narcissism are more perilous. By rethinking narcissism as a complex structure of self-relation through the Other, the book reveals the necessity of an im-possible self-love. -- Provided by publisher